2021
DOI: 10.1021/acsmedchemlett.0c00641
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Activity and Brain Kinetics Relationships of 18F-Labeled Benzimidazopyridine Derivatives as Tau PET Tracers

Abstract: Noninvasive imaging of tau aggregates with a positron emission tomography (PET) tracer is useful for the diagnosis and staging of Alzheimer's disease (AD). Recently, we found that benzimidazopyridine (BIP) is an attractive scaffold for developing PET and single photon computed emission tomography tracers targeting tau aggregates. In this study, we designed and synthesized five novel 18 F-labeled compounds with various substituted groups or atoms at the 7-position of the BIP scaffold. In in vitro autoradiograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Changing the position and number of N atoms in existing tracers is expected to overcome the shortcomings of existing tracers. With modification, the ligand’s site of interaction and hydrophilicity will be changed, which might contribute to better properties for PET tracers without affecting previous affinity, such as modifying PK11195 to ER176 for translocator protein imaging and AV1451, PI-2620, and RO-948 for tau imaging. , Meanwhile, the substitution is more efficient for the development of new tracers than trying to produce a completely new moiety. Benzothiophene and stilbene structures are two major skeletons for Aβ tracers.…”
Section: Resultsmentioning
confidence: 99%
“…Changing the position and number of N atoms in existing tracers is expected to overcome the shortcomings of existing tracers. With modification, the ligand’s site of interaction and hydrophilicity will be changed, which might contribute to better properties for PET tracers without affecting previous affinity, such as modifying PK11195 to ER176 for translocator protein imaging and AV1451, PI-2620, and RO-948 for tau imaging. , Meanwhile, the substitution is more efficient for the development of new tracers than trying to produce a completely new moiety. Benzothiophene and stilbene structures are two major skeletons for Aβ tracers.…”
Section: Resultsmentioning
confidence: 99%
“…[ 18 F]IBIPF1 (Figure 9b) showed high initial uptake in mouse brains (6.2% ID/g at two min post-injection) and fast brain washout [206]. Biodistribution studies of [ 125 I]21 and [ 125 I]22 in normal mice likewise showed favorable pharmacokinetics, potentially superior to that of ([ 125 I]BIP-NMe 2 , Figure 9a) [203]. Overall, this study represented two new scaffolds for developing further novel tau tracers, which remain to be studied in AD.…”
Section: Radioiodinated Benzoimidazopyridine (Bip) Derivativesmentioning
confidence: 97%
“…(a): [ 125 I]BIP-NMe 2 , (b): [ 18 F]IBIPF1, (c): [ 18 F]IBIPF2, (d): [ 18 F]Br-BIPF, (e): [ 18 F]Cl-BIPF, (f): [ 18 F]Me-BIPF, (g): [ 18 F]OMe-BIPF. Introducing halogens, methoxy, or methyl groups to the 7-position of BIP scaffold resulted in various compounds, including [ 18 F]Br-BIPF (Figure 9d, 7-bromo-N-(2-[-18 F]fluoroethyl)-N-methylbenzo[4,5]imidazo[1,2-a]pyridin-3-amine), [ 18 F]Cl-BIPF (Figure 9e, 7-chloro-N-(2-[ 18 F]fluoroethyl)-N-methylbenzo[4,5]imidazo[1,2-a]pyridin-3-amine), [ 18 F]Me-BIPF (Figure 9f, N-(2-[ 18 F]fluoroethyl)-N,7-dimethylbenzo[4,5]imidazo[1,2-a]pyridin-3-amine), and [ 18 F]OMe-BIP (Figure 9g, N-(2-[ 18 F]fluoroethyl)-7-methoxy-N-methylbenzo[4,5]imidazo[1,2-a]pyridin-3amine)[203].Autoradiography studies have indicated the higher effect of modifications in the 3-position of the BIP scaffold on affinity to tau aggregates than modifications of the 7-position[202]. However, [ 18 F]Br-BIPF (Figure9d), [ 18 F]Cl-BIPF (Figure9e), [ 18 F]Me-BIPF (Figure9f), and [ 18 F]OMe-BIP (Figure9g) have also shown appropriate binding to tau aggregates in AD brain sections[201,202].…”
mentioning
confidence: 99%